Analisa pengaruh variasi media quenching dan penambahan silikon pada paduan al-si remelting velg sepeda motor terhadap sifat fisik dan mekanis - Andi Septiadi; Teguh Triyono; Joko Triyono (Badan Kerja Sama Teknik Mesin Indonesia, 2016)
The disposition of aluminum is lightweight, high corrosion resistance, low density, can be formed properly, and a high conductivity both thermal and electrical. Remelting process has a defect (porosity) however the weakness of remelting is ability of a material decreases along with the treatment. The additional silicon on the materials aim to improve the characteristics. This research was done to find out the effect of silicon variant and it had been quenched with a variant of cooling media. The material that had been used was Aluminum-Silicon (Al-Si) from velg motorcycle waste. Casting processing method that was done using sand casting. The ingredients of remelting Al-Si with silicon addition (Si) are 2%, 4% and 6%. The specimen was formed based on JIS Z 2202 for tenstile strength. Heat treatment had been performed on the specimen with temperatur 520oC for 1 hour, and quenched on water and oil as a cooling media. Testings were performed; ingredient test, tensile test, hardness test, dan micro structure. he result testing of tensile strength and hardness showed the average value increased with additional silicon and quenching treatment. Tenstile strength and hardness specimen using a water as a cooling media have a better value than an oil SAE 40 as a cooling media.